2022
DOI: 10.1186/s12957-021-02484-z
|View full text |Cite
|
Sign up to set email alerts
|

Gasless, endoscopic trans-axillary thyroid surgery: our series of the first 51 human cases

Abstract: Background The safety of gasless endoscopic trans-axillary thyroid surgery is still undetermined. Methods Clinical findings and postoperative complications of patients who had undergone trans-axillary thyroid surgery due to thyroid cancer and thyroid nodules were retrospectively studied. The sensory change and paralysis results from this technique and patients’ satisfaction with the cosmesis were also studied. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…To compare our technique with previous GUA approach reports based on the endoscopic platform, we have reviewed the literature and summarized it in Table 3. The mean age of patients received ranged from 35 to 42.6 (20,(23)(24)(25)(26)(27)(28). The mean BMI ranging The settlement of RLN.…”
Section: Discussionmentioning
confidence: 99%
“…To compare our technique with previous GUA approach reports based on the endoscopic platform, we have reviewed the literature and summarized it in Table 3. The mean age of patients received ranged from 35 to 42.6 (20,(23)(24)(25)(26)(27)(28). The mean BMI ranging The settlement of RLN.…”
Section: Discussionmentioning
confidence: 99%
“…During the last century, the number of detected thyroid carcinomas has increased significantly 6 . While conventional open thyroidectomy is still the standard procedure for thyroid carcinoma patients, endoscopic thyroidectomy is gradually becoming accepted for patients with cosmetic needs 7 . The proportion of endoscopic thyroidectomy will be higher in the future for the reason that PTCs occur in more and more young patients with a female predominance 8 .…”
Section: Discussionmentioning
confidence: 99%
“…These approaches require an additional level of expertise and should therefore be performed by surgeons performing large numbers of thyroid and endoscopic procedures ( 9 ). Transaxillary, bilateral axillo-breast approach (BABA) robotic, transoral, and endoscopic total mammary areola approaches have been reported to achieve endoscopic thyroidectomy in our center ( 4 , 10 , 11 ). We further evaluated the safety and effectiveness of these endoscopic approaches compared with conventional approaches and showed that endoscopic procedures were similar to conventional procedures in safety, efficacy, and tumor recurrence but with better cosmetic results and higher patient satisfaction rates regarding quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, almost all patients who underwent gasless endoscopic thyroidectomy in our center complained of paraesthesia and stiffness around the anterior chest area and SCM one week after surgery. However, discomfort was relieved over time, and the results were acceptable ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation